The Effect of Gender Inequality in Education, Labor Force Participation and Economic Opportunity on the Income Distribution of India - Athena Chantel Angeles; Samantha Jean Donaire; Rogie Benedict Reyes; Ronaldo Cabauatan (Universitas Cokroaminoto Palopo, 2021)
This study analyzes the degree of gender inequality in education, labor force participation, and economic opportunity and its relationship with income distribution in India. The study aims to discern if a negative relationship exists between gender inequality in the multi-dimensional context and income distribution. Certain studies prove that gender wage inequality and income distribution exhibit a positive correlation for export-oriented economies wherein women provide most of the labor for the export sector. However, it is not the same case for gender inequality in the education and labor force. The theoretical model is based on Becker’s net earnings model but adjustments are done to the variables used. Using annual time-series data provided by the World Bank, World Inequality Database, and Human Development Report, the researchers assume that gender inequality in wages, mean and expected years of schooling, and labor force participation rate affects income distribution across the top, middle, and bottom classes in India. In addressing this issue, the purpose of the study is to form policy recommendations to reduce inequalities in gender across India’s education and economic sector.